Antecedents and Consequences of Trust as a Multidimensional Construct. Cross-Country Analysis in the Luxury Retail Sector; [Antecedentes y Consecuencias de la Confianza Como Un Constructo Multidimensional. Análisis Transnacional en el Sector Minorista del Lujo] - Marinao-Artigas, E; Laroze-Prehn, D (Institute of Applied Business Economics, 2023)
The objective of this study is to understand the role of the multidimensional trust of a luxury brand as an antecedent of consumer satisfaction and a consequence of reputation and familiarity, considering -in turn-that reputation and familiarity can be a consequence of the consumer’s cognitive and affective experiences. A cross-country analysis in the luxury retail sector was carried out. Association relationships between variables are tested by a model of structural equations. For this, a transnational analysis has been carried out in the luxury retail sector. A non-probabilistic sample was used in this study. 1058 people were interviewed, 608 consumers in Santiago (Chile) and 450 in Madrid (Spain). The key role played by the multidimensional trust of a luxury brand as an antecedent of satisfaction and consequence of reputation and familiarity is confirmed. When observing the reputation and familiarity of a luxury brand as a result of the cognitive and affective experiences of the consumer, differences between Chile and Spain have been discovered. Managers can not only use the brand’s own characteristics to differentiate themselves from the competition, but they can also do so through the multi-dimensional trust of the luxury brand. © This article is distributed under the terms of the Creative Commons Atribution 4.0 Internacional License